1981
DOI: 10.1126/science.214.4525.1081
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Storage Materials: Properties and Possibilities

Abstract: The physics, chemistry, and possible applications of the storage of hydrogen in intermetallic reservoirs are discussed. Storage in the form of intermetallic hydrides can be safe and, where hydrogen has some special value as a fuel, economical. New pumps and refrigerators based on the heat of sorption of the hydrogen into the intermetallic are approaching commercial viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…Although the focus is on recent developments and future directions, there is a long and distinguished history of hydrogen research that laid the foundations for the current surge of research activity. 4 …”
Section: Carriers Storage and Transformation • Hydrogen And Fuel Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the focus is on recent developments and future directions, there is a long and distinguished history of hydrogen research that laid the foundations for the current surge of research activity. 4 …”
Section: Carriers Storage and Transformation • Hydrogen And Fuel Cellsmentioning
confidence: 99%
“…If Li 2 NH could be destabilized to release the remaining H, the storage capacity would be 9.6%, high enough for hydrogen-powered transportation. LiBH 4 and MgH 2 are another destabilization couple, with a storage capacity of 11.5%. 34 The promise of destabilized hydrides for storage is the much larger number of paired (or multiple) hydrides than single hydrides might provide effective storage.…”
mentioning
confidence: 99%
“…Hydrides can store more hydrogen per unit volume than liquid or solid hydrogen [3] and have potential applications for heat management systems such as cryocoolers and heat pumps [4][5][6][7] besides numerous other applications. By using a suitably matched pair of hydrides with high and low equilibrium pressures, the system can be made to operate continuously to make up the working cycle of a metal hydride heat pump (MHHP).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that hydrides offer an efficient and safe way for storing hydrogen [2]. Unfortunately, high volumetric hydrogen storage capacity in most of these hydrides is being offset by their low gravimetric hydrogen storage capacity, which is generally to be of the order of 1-2 wt.% [3]. One of the ways to overcome this difficulty is using high hydrogen content compounds such as MH x (e.g.…”
Section: Introductionmentioning
confidence: 98%